Klinik Penulisan Artikel Ilmiah Sebagai Upaya Peningkatan Kemampuan Menulis Artikel Ilmiah Di Nanga Pinoh - Rindah Permatasari; Linda Dwi Saputri; Wahyu Septiadi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The development of teaching profession is the focus of the government which is always campaigned for the creation of education 4.0. Teachers are not only required to be an educator, but also to be able to develop the teaching profession, one of which is being able to write scientific papers. Based on the results of observations and interviews conducted at SMP N 2 Nanga Pinoh, identified problems faced by partners, namely: (a) Teachers are constrained in writing scientific papers; (b) Teachers do not understand the technique of writing scientific papers; (c) Teachers lack understanding in designing and the stages in classroom action research. This activity aims to improve the understanding and skills of teachers in writing scientific articles. PkM activities are carried out in the form of training with lecture methods, question and answer, group discussions and the practice of making scientific articles. Participants in this training were 20 teachers at SMP N 2 Nanga Pinoh. The test is used to see the teacher's understanding and response to writing scientific papers. The initial test showed an average value of 45.5. Of the 20 participants, only 2 participants scored 70, which means that the participants understood the essence of writing scientific articles by 70%. After the clinical writing of scientific articles was carried out, there were 3 participants who had scores below 70, namely ASR, MW and SH, 17 other participants had understood scientific articles by 70% and the average final test was 74.5. Overall, participants' understanding of the technique of writing scientific articles has increased by 29 points or when viewed from the Gain (N-Gain) normality test of 0.53 in the Medium category. This means that after this activity, on average, the participants experienced an increase in the teacher's understanding and skills in writing scientific articles.